Benign acute childhood myositis in Qassim, Kingdom of Saudi Arabia; A retrospective study - Yasir S. Alkhalifah; Yazeed A. Alghasham; Haitham M. Jarikji; Ammara Naeem; Mansour S. Alzahrani; Hussein Omari Sombi (Saudi Journal for Health Sciences)
Background: Benign acute childhood myositis (BACM) is a rare muscle disorder generally encountered by middle school students. Severe calf pain, tenderness, and difficulty to walk are the clinical presentation of BACM cases. Aims: The objective of the study was to assess the epidemiological, clinical, and laboratory characteristics of BACM in the children diagnosed in the Qassim-Buraidah, Saudi Arabia. Settings and Design: This retrospective study was conducted in the Province of Qassim-Buraidah, Saudi Arabia. Subjects and Methods: BACM cases reported between January 2020 and January 2024 were included in the study. Demographical, clinical, and laboratory parameters were collected from medical records and analyzed. Statistical Analysis Used: Data were statistically analyzed using Statistical Package for the Social Sciences (SPSS v. 23). Results: A total of 297 BACM cases were found and included in the study. The median age was 6 years which was varying between 1 and 13 years. Cough was the most common prodromal symptom. In the clinical symptoms, bilateral calf pain and calf tenderness were highly prevalent among males compared to females. In the laboratory findings, creatinine level was found to be disturbed in 3 (1.1%) patients, whereas C-reactive protein outside the normal range was found among 72.8% and creatine kinase (CPK) among 51.8%. Elevated CPK and leukopenia were found significantly high among males compared to females (P = 0.001) and (P = 0.036), respectively. Conclusion: In this study, prodromal and clinical symptoms were highly evident among males compared to females. Furthermore, some laboratory parameters were found to be outside normal ranges in males compared to females, pointing toward potential gender-specific differences in the manifestation of BACM. Further research focusing on these differences and whether they impact disease severity or outcome would be recommended.